Morphotectonic Analysis along the Northern Margin of Samos Island, Related to the Seismic Activity of October 2020, Aegean Sea, Greece - Paraskevi Nomikou; Dimitris Evangelidis; Dimitrios Papanikolaou; Danai Lampridou; Dimitris Litsas; Yannis Tsaparas; Ilias Koliopanos (Geosciences, 2021)
On 30 October 2020, a strong earthquake of magnitude 7.0 occurred north of Samos Island at the Eastern Aegean Sea, whose earthquake mechanism corresponds to an E-W normal fault dipping to the north. During the aftershock period in December 2020, a hydrographic survey off the northern coastal margin of Samos Island was conducted onboard R/V NAFTILOS. The result was a detailed bathymetric map with 15 m grid interval and 50 m isobaths and a morphological slope map. The morphotectonic analysis showed the E-W fault zone running along the coastal zone with 30–50° of slope, forming a half-graben structure. Numerous landslides and canyons trending N-S, transversal to the main direction of the Samos coastline, are observed between 600 and 100 m water depth. The ENE-WSW oriented western Samos coastline forms the SE margin of the neighboring deeper Ikaria Basin. A hummocky relief was detected at the eastern margin of Samos Basin probably representing volcanic rocks. The active tectonics characterized by N-S extension is very different from the Neogene tectonics of Samos Island characterized by NE-SW compression. The mainshock and most of the aftershocks of the October 2020 seismic activity occur on the prolongation of the north dipping E-W fault zone at about 12 km depth.